Biosynthesis of Nodulisporic Acids: A Multifunctional Monooxygenase Delivers a Complex and Highly Branched Array. (9th November 2022) - Richardson, Alistair T.; Cameron, Rosannah C.; Stevenson, Luke J.; Singh, A. Jonathan; Lukito, Yonathan; Berry, Daniel; Nicholson, Matthew J.; Parker, Emily J.
Abstract: Nodulisporic acids (NAs) are structurally complex potent antiinsectan indole diterpenes. We previously reported the biosynthetic gene cluster for these metabolites in Hypoxylon pulicicidum and functionally characterised the first five steps of the biosynthetic pathway. Here we reveal a highly complex biosynthetic array, furnishing multiple end products through expression of cluster components in Penicillium paxilli . We show that seven additional cluster‐encoded gene products comprise the biosynthetic machinery that elaborate precursor NAF in this highly branched pathway. The combined action of these enzymes delivers 37 NA congeners including four major end products, NAA, NAA1, NAA2 and NAA4 . The plethora of intermediates arises due to modification of the carboxylated prenyl tail by a single promiscuous P450 monooxygenase, NodJ, a pivotal branchpoint enzyme which produces four distinct biosynthetic products giving rise to the complex metabolic grid that characterises NA biosynthesis. Abstract : Nodulisporic acids are structurally complex potent antiinsectan natural products produced by the filamentous fungus Hypoxylon pulicicidum . A gene cluster, consisting of 13 genes, has been identified and biosynthetic machinery functionally characterised. This work reveals a highly complex biosynthetic array, furnishing multiple nodulisporic acid congeners. The variation arises due to the action of a single promiscuous P450 monooxygenase, NodJ.